Research on the Effects of the Chronic Treatment With Different Doses of Urocortin 2 in Heart Failure Rats. Issue 2 (26th June 2019) - Yang, Li-Zhen; Chen, Ying
Corticotropin-releasing factor (CRF) receptor type 2 (CRF2 ) exists in both cardiomyocytes and neurocytes. The purpose of this research was to explore if chronic treatment with urocortin 2 (UCN2), a CRF2 receptor agonist, at different doses can improve prognosis and regulate the expression of CRF2 receptor and calcium handling proteins without any adverse effects on behavior in heart failure. Heart failure was established in Sprague-Dawley rats and was confirmed by echocardiography. Heart failure rats were injected intraperitoneally with UCN2 (5, 10, or 20 µg·kg −1 ·d −1 ) for 30 days. Survival rate, cardiac function, expressions of cardiac CRF2 receptor, RyR2, SERCA2, and hypothalamic and hippocampal c-FOS, CRF receptor type 1 (CRF1 ) and CRF2 receptor were determined. Behavior was evaluated by Morris Water-Maze and Open-Field tests. Results showed that chronic peripheral UCN2 treatment improved survival rate in a dose–response manner and increased cardiac function and expression of CRF2 receptor and SERCA2 in heart failure, especially at the high dosage. Moreover, cellular-fos (c-FOS), CRF1 receptor, and CRF2 receptor expressions of both hypothalamic and hippocampal tissues were significantly increased in high dosage group. Furthermore, the behavior tests suggested that chronic UCN2 treatment did not exacerbate stress/anxiety-like behavior in HF. In conclusion, chronic peripheral treatment with UCN2 increases survival in a dose–response manner in heart failure rats without inducing stress/anxiety-like behavior.